Fisheries case (United Kingdom v. Norway), judgement of 18th Decembe 1951 - International Court of Justice (The Hague : ICJ, 1951)
English and French
Keywords: Foreign policy -- Great Britain; Foreign policy -- Norway; Great Britain -- Boundaries -- Norway; Norway -- Boundaries -- Great Britain